PERAN PENYULUH KANTOR URUSAN AGAMA KECAMATAN ANGGERAJA DALAM MEBERIKAN BIMBINGAN MANASIK HAJI KEPADA CALON JAMAAH HAJI (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This study discusses the role of extension workers in providing ritual guidance to prospective pilgrims in Anggeraja District, Enrekang Regency. The purpose of this study is to find out the role of an extension worker at the Office of Religious Affairs in providing guidance on the rituals of Hajj so that pilgrims have a better understanding of the Hajj before performing Hajj. This study uses a qualitative type of research with a management approach, especially the role of the Anggeraja Religious Affairs Office instructor in providing manasic guidance. The data collection method used is the method of observation, interviews, and documentation. Data processing and analysis techniques are carried out with data reduction, data display, and conclusion drawing/verification. The results of this study indicate that the role of the extension worker at the Office of Religious Affairs, Anggeraja Subdistrict, Enrekang Regency in providing guidance on Hajj rituals, namely; 1) planning the guidance for Hajj rituals at the Anggeraja District Religious Affairs Office, namely determining everything that will be needed when the Hajj rituals are carried out and carrying out all activities in accordance with the directions from the District Ministry of Religion Office. 2) organizing the guidance for Hajj rituals at the Office of Religious Affairs, Anggeraja Sub-district, Enrekang Regency, consisting of the chairman (head of KUA Anggerja) and members (KUA Anggerja instructor). 3) the implementation of guidance for Hajj rituals at the Office of Religious Affairs, Aggeraja Sub-district, Enrekang Regency in accordance with what has been planned. 4) supervision of the guidance for Hajj rituals at the Office of Religious Affairs in the District of Anggeraja is carried out by the Office of the Ministry of Religion of the Regency of Enrekang. Supporting factors and inhibiting factors for guidance on Hajj rituals at the Office of Religious Affairs, Anggeraja District, Enrekang Regency, namely supporting factors, the presence of pilgrims, facilities, and infrastructure, and good delivery methods besides that. pilgrims who are less disciplined in the rituals of Hajj.